Unmet health‐care needs and human rights-A qualitative analysis of patients' complaints in light of the right to health and health care - Annelie J. Sundler; Laura Darcy; Anna Råberus; Inger K. Holmström (Wiley, 2020)
Abstract Background This study focuses on patient complaints from a human rights perspective. Despite the UN Convention on Human Rights being widely recognized, it has not previously been examined in relation to patients' complaints on health care. A human rights perspective and the right to the highest attainable standard of health are a major sustainability challenge in health care today. Previous research points to patients' complaints as a growing concern for health‐care organizations, and the handling of this concern can lead to improvement in health‐care services. Objective The aim was to analyse patients' complaints on health‐care services and to examine expressed needs for health care from a human rights perspective. Methods In this descriptive study, a random sample of 170 patient complaints about Swedish health‐care services were qualitatively analysed from a human rights perspective. Results The complaints are described in three themes: the right to available and accessible health‐care services, the right to good quality health‐care services and the right to dignity and equality in health care. Questions of availability, accessibility, acceptability and quality are highlighted by patients and/or relatives making complaints on health‐care services. Discussion and Conclusion This study emphasizes the human right to health in relation to patient complaints. Findings indicate that this right has been breached in relation to availability, accessibility, acceptability and quality in health‐care services. Further debate, education and investigations are necessary to ensure that patients' rights to health and health care not be taken for granted.